Geospatial threat measurement : an analysis of the threat the diatom Didymosphenia geminata poses to Canterbury, New Zealand : a thesis submitted in fulfilment of the requirements for the degree of Master of Philosophy in Geographic Information Systems in Massey University, Palmerston North - Thornley, Norman John (Massey University, 2009)
This thesis provides analysis of the threat Didymosphenia geminata poses to the Canterbury Conservancy of the Department of Conservation More specifically, it examines the relationship between Values, Risk and Hazard to measure the degree of threat posed by the diatom. This is the first time this type of Threat Analysis has been applied to such a problem in this region; and so will provide an important insight into the validity of the application of this methodology to an alien invasive threat. Moreover, it is the first time Values. Risk and Hazard have been modelled together to give an over all threat classification in this context. Risk mitigation is one of the variables that can be measured, managed and priced; factoring this into the model is also discussed. Qualitative and quantitative Values and Risk information is provided by Department of Conservation staff; some from their local knowledge and some from biodiversity datasets which have been collected over time. The Risk data is supplemented by fishing access data supplied by the two local Fish and Game Council Offices. Where available, further Values and Risk data has been gleaned from existing datasets in order to supplement the existing data. The Hazard data is taken from the work done by NIWA in 2005 and 2007; the latter being generated after field surveys were conducted on D. geminaia infected sites in the South Island.
Keywords: Mathematical models; Geographic information systems; Spatial analysis (Statistics); Didymo; New Zealand; Rivers -- Canterbury